2013
DOI: 10.1111/pace.12292
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Anxiety and Depression on Symptoms Attributed to Atrial Fibrillation

Abstract: Our results extend previous studies demonstrating that anxiety and depression are associated with worsened AFSS. Antiarrhythmic drug therapy or catheter ablation reduces AFSS but does not affect depression and anxiety symptoms. To achieve more comprehensive AF symptom relief, treatment of both AF and psychological comorbidities may be beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 27 publications
3
59
1
2
Order By: Relevance
“…37 Similarly, increased severity of depression and anxiety are associated with increased AF symptom severity (p<0.001). 31 Palpitations were significantly more common among the women in our study, and are known to be influenced by neuropsychiatric variables. 34 It is plausible that differences in neuropsychiatric variables influenced the number of men versus women that experienced the heart cluster.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…37 Similarly, increased severity of depression and anxiety are associated with increased AF symptom severity (p<0.001). 31 Palpitations were significantly more common among the women in our study, and are known to be influenced by neuropsychiatric variables. 34 It is plausible that differences in neuropsychiatric variables influenced the number of men versus women that experienced the heart cluster.…”
Section: Discussionmentioning
confidence: 53%
“…Previous reports indicate younger age and female gender are associated with an increased frequency and severity AF symptoms. 31,36 However, Sears et al 32 found that age and gender were not significantly associated with the number of AF symptoms reported. Our results indicate that age and gender are indeed non-modifiable characteristics that influence certain aspects of symptom perception, specifically symptom clustering.…”
Section: Discussionmentioning
confidence: 99%
“…The first phase of assistance and psychological intervention begins with the assessment of the mental state of the patient. Clinical psychologist looking after the patient performs an initial psychological diagnosis and conducts psychological therapy aimed at: − helping the patient to control fear, distress, sometimes strong anxiety, − ensuring the patient about his or her safety, − reducing the mental tension, − providing mental support (4,(10)(11)(12)(13)(14). The psychological impact is mainly based on informing the patient about the place and the therapy conducted, explaining the peculiarities of treatment in a clinic/cardiology ward, informing the patient about the need to monitoring the electrical activities of the heart (EKG), and the need to monitoring blood pressure.…”
Section: Methodsmentioning
confidence: 99%
“…Anxiety was an important predictor of arrhythmia-specific symptoms and HRQoL at baseline, but did not influence improvement of symptoms and HRQoL after RFA. Previous studies have shown that anxiety is strongly correlated with AF symptoms 69,106 , and that a depressed mood and worry can increase perceptions of AF symptom burden and cause disengagement from daily activities 107 . Still, their relationship can be regarded as a "the egg or the chicken" situation, i.e.…”
Section: Quality Of Lifementioning
confidence: 99%